The Effect of Linen Management on the Safety and Health of Laundry Workers at the “X” Hospital in Bandung - Ceria Febiana; Nurul Khotimah (International Journal of Business, Economics, and Social Development, 2023)
This study aimed to acknowledge the effect of linen management on the health and safety of laundry workers at ‘X’ Hospital in Bandung. The method of this research was a quantitative research method with a descriptive approach. Data collection was carried out by means of field observations, questionnaires, literature studies and internet browsing. The results showed that the effect of linen management on the safety and health of laundry workers was 37.5%, while 62.5% of the effect was influenced by other independent variables which were not included in this study. In the hypothesis test conducted by the author, the results of the t test were 3.549, which means t count > t table (3.549 > 2.776) so that there is a positive and significant influence between linen management and the health and safety of laundry workers at Muhammadiyah Bandung Hospital. The research found the following problems: 1) poor coordination with the nursing department so that errors still often occur in sorting linen, 2) lack of adherence to procedures, especially personal protective equipment so that it can cause washing workers to be exposed to chemical fluids, and 3) the process of recording all incidents or potential accidents do not go well in the laundry unit. The suggestions given to fix the problem are: 1) to improve communication with other units, 2) to carry out a level of supervision regarding compliance with standard operating procedures and personal protective equipment (PPE), and 3) to record all things that may become potential accidents in the report.